2020
DOI: 10.3386/w27660
|View full text |Cite
|
Sign up to set email alerts
|

This Time It's Different: The Role of Women's Employment in a Pandemic Recession

Abstract: In recent US recessions, employment losses have been much larger for men than for women. Yet, in the current recession caused by the Covid-19 pandemic, the opposite is true: unemployment is higher among women. In this paper, we analyze the causes and consequences of this phenomenon. We argue that women have experienced sharp employment losses both because their employment is concentrated in heavily affected sectors such as restaurants, and due to increased childcare needs caused by school and daycare closures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(177 citation statements)
references
References 54 publications
4
162
3
8
Order By: Relevance
“…Coupled with an unsupported childcare sector (Lewis and West 2017), a significant reduction in female participation in the labour force and an increase in the gender pay gap could last for a number of years (Alon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled with an unsupported childcare sector (Lewis and West 2017), a significant reduction in female participation in the labour force and an increase in the gender pay gap could last for a number of years (Alon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Bandiera et al (2019) have shown that the impact of these closures were long-lasting: 13 months after the start of the crisis 63% of men had lockdowns (e.g. tourism and hospitality) and the gendered norms related to childcare when schools and nurseries close coupled with restrictions to kinship care (Alon et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some papers have documented that more economically vulnerable individuals-such as those with lower income and educational attainment [Cajner et al, 2020;Chetty et al, 2020;Shibata, 2020], minorities [Fairlie et al, 2020], immigrants Borjas and Cassidy [2020], and women [Alon et al, 2020;Del Boca et al, 2020;Papanikolaou and Schmidt, 2020]-have been impacted more harshly during the early phases of the COVID-19 pandemic, both in the US and other countries [Alstadsaeter et al, 2020;Béland et al, 2020]. One reason is that lower paid workers are often unable to perform their jobs while working from home [Dingel and Neiman, 2020;Gottlieb et al, 2020].…”
Section: Related Literaturementioning
confidence: 99%
“…Our paper is closely related to studies that analyze the labor market effects of the epidemic. (see Alon et al, 2020;Boar and Mongey, 2020;Fang et al, 2020;Giupponi and Landais, 2020;Gregory et al, 2020;Kapicka and Rupert, 2020;Mitman and Rabinovich, 2020). Relative to this literature, we jointly study UI and payroll subsidies and analyze their differential effects on the labor market.…”
Section: Introductionmentioning
confidence: 99%